Experimental Investigation of a Medium Temperature Single-Phase Thermosyphon in an Evacuated Tube Receiver Coupled With Compound Parabolic Concentrator - Akhter, Javed; Gilani, S. I.; Al-Kayiem, Hussain H.; Mehmood, Mubbashar; Ali, Muzaffar; Ullah, Barkat; Alam, Mohammad Azad; Masood, Faisal (Frontiers in Energy Research, 2021)
The integration of evacuated tube receivers with non-imaging compound parabolic concentrators (CPCs) operating in thermosyphon mode provides the opportunity to deliver solar thermal energy in the medium temperature range that is suitable for many industrial applications. However, the performance of single-phase thermosyphon in the medium temperature range has not been comprehensively investigated. This paper presents the design, development, and performance evaluation of a single-phase thermosyphon in an evacuated tube receiver integrated with a modified CPC solar collector. The thermohydraulic performance of the developed system is evaluated in the tropical climate using Therminol-55 oil as heat transfer fluid. The results demonstrate that the maximum outlet temperature reached over 120°C using thermal oil as heat transfer fluid while it remained at 100°C in case of water. The zero-loss thermal efficiency reached up to 70% on a clear sky day. Comparing the thermal performance of the developed CPC collector with an existing model of a non-concentrating collector showed much improvement at elevated temperatures. This indicates that this system can effectively operate in tropical weather conditions to provide sustainable solar thermal energy in the medium temperature range.